STRATEGI PENGEMBANGAN ASURANSI TERNAK SAPI - Nina Sari An-nisa; Rizal Syarief; Gendut Suprayitno (Jurnal Manajemen & Agribisnis, 2015)
Livestock is one of the agricultural Subsectors, which has a strategic role in economic matters in Indonesia. However, livestock faces a lot of risks, which often cause loss for the livestock business agents, especially the breeders. This research aimed to analyze a development strategy on livestock insurance pilot project. The development of the strategy is important for a company in achieving its objectives. This research also aimed to analyze external and internal factors affecting the cattle insurance pilot project implementation and to analyze the company position so that the objectives of the company on cattle insurance pilot project implementation could be determined. Furthermore, this research aimed to design a strategy on the implementation of livestock insurance pilot project, and a case study was used as the research method. The result showed that there were some external and internal factors affecting the development of livestock insurance such as brand image and company performance. The position of the company in the development of livestock insurance is to hold and maintain its position by using the strategic recommendations i.e. market penetration and product development strategy. There are 8 alternative strategies for the development of cow insurance obtained based on the strategy analysis, and there is one suitable alternative strategy obtained by SWOT analysis. The priority strategy obtained in this research by QSPM analysis is given to companies as a recommendation to establish cooperation between companies and the ministry of agriculture to socialize the implementation of livestock insurance and good breeding practice. Keyword: development strategy, cow insurance, pilot project, PT Asuransi Jasa Indonesia, QSPMABSTRAKPeternakan merupakan salah satu subsektor pertanian yang mempunyai peran strategis dalam perekonomian di Indonesia. Namun dalam pelaksanaannya subsektor peternakan menghadapi berbagai risiko yang tidak jarang memberikan kerugian bagi pelaku subsektor peternakan khususnya peternak. Penelitian ini bertujuan menganalisis faktor lingkungan yang berpengaruh pada pelaksanaan pilot project asuransi ternak sapi pada PT Asuransi Jasa Indonesia (Persero). Penelitian ini juga dilakukan untuk mengetahui posisi perusahaan dalam pelaksanaan pilot project, sehingga dapat ditentukan tujuan perusahaan dan selanjutnya akan ditentukan strategi yang sesuai untuk diimplementasikan oleh PT Asuransi Jasa Indonesia sebagai pelaksana pilot project asuransi ternak sapi. Metode yang digunakan pada penelitian ini adalah metode studi kasus. Hasil yang diperoleh dari penelitian ini yaitu diketahui beberapa faktor lingkungan yang paling berpengaruh pada pelaksanaan pilot project asuransi ternak sapi diantaranya adalah kinerja dan brand image perusahaan serta adanya payung hukum berupa UU No 19 tahun 2013. Posisi perusahaan dalam pelaksanaan pilot project ini adalah dalam posisi pertahankan dan pelihara dengan rekomendasi strategi yaitu strategi penetrasi pasar dan strategi pengembangan produk. Pada penelitian ditentukan delapan alternatif strategi yang diperoleh dengan alat analisis SWOT dan ditentukan satu prioritas strategi yang diperoleh dengan alat analisis QSPM sebagai rekomendasi kepada perusahaan yaitu perusahaan melakukan kerjasama dengan Kementerian Pertanian untuk sosialisasi asuransi ternak sapi dan penerapan good breeding practice.Kata kunci:  strategi pengembangan, asuransi ternak sapi, pilot project, PT Asuransi Jasa Indonesia, QSPM